Research on the support model of large equipment emergency spare parts under fuzzy demand - Jianhua Yang; Zhichao Ma; Yang Song (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: Aim at making a scheme for emergency spare parts the support problem when large equipment spare parts supply network faced with large-scale emergency events. Design/methodology/approach: In order to analyze the model, we establish the spare parts security model under network supply conditions to respond emergency in case of fuzzy demand. And in end of the paper, we adopt an improved genetic algorithms to solve the problem. Findings: Considering emergency spare parts support problem from three aspects including satisfaction of time, satisfaction of demand and emergency cost constraints, which makes decision-making process more accord with reality condition, we can get a more realistic solution for the decision makers. Originality/value: Considering the occurrence of emergency and adopting information entropy theory to order the weight of emergency maintenance station in priority sequence, this paper presented emergency response time and demand satisfaction function, which uses the time, demand satisfaction and the cost restrictor as main objective, we have constructed the spare parts support model under fuzzy demand to solve emergency events, having expanded the scope of solution.
Keywords: 650; fuzzy demand; satisfaction index; personality; emergency spare parts